2018
DOI: 10.1111/ijd.13938
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing diabetes mellitus in patients with porphyria cutanea tarda

Abstract: The prevalence of diabetes mellitus is increased in patients with porphyria cutanea tarda. Different tests are available for diagnosing and screening for type II diabetes mellitus, however choosing the most suitable test is challenging. The pitfalls in the different tests along with the interfering comorbidities and treatments concerning patients with porphyria cutanea tarda complicate diagnosing these patients with diabetes mellitus. HbA1c, fasting glucose, or oral glucose tolerance are the current available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…Our expectation was based on previous studies showing that patients with PCT had a high prevalence of diabetes and high risk of stroke. We cannot explain this discrepancy between older studies and ours [10][11][12]17 .…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Our expectation was based on previous studies showing that patients with PCT had a high prevalence of diabetes and high risk of stroke. We cannot explain this discrepancy between older studies and ours [10][11][12]17 .…”
Section: Discussioncontrasting
confidence: 85%
“…Moreover, PCT patients also have an increased prevalence of impaired glucose tolerance and diabetes mellitus. The association between PCT and impaired glucose metabolism is not fully understood, but possibly implicates iron overload; a previous study showed that PCT patients with persistently high ferritin levels were more likely to develop impaired glucose metabolism and diabetes 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…84 Administration of estrogens via transdermal route is safe and recommended for at-risk women previously treated for PCT. 83 Hepatic siderosis, 6,83 systemic lupus erythematosus, 85 end-stage renal disease on hemodialysis, 86 diabetes mellitus, 87 and hematologic malignancies 88 are all associated with the development of PCT, 69,76 as is exposure to toxins such as polychlorinated biphenyls, hexachlorobenzene, and other polyhalogenated hydrocarbons that significantly induce CYP enzymes. 89…”
Section: Susceptibility Factorsmentioning
confidence: 99%